Polylactic acid composite material and preparation method thereof
By adjusting the composition distribution ratio and particle size in the polylactic acid composite material and improving its crystallization speed, the problem of insufficient heat resistance of polylactic acid composite material is solved, and the thermal deformation temperature and impact strength are improved.
Patent Information
- Application Number
- CN202411735631.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-05-02
AI Technical Summary
The thermal resistance of polylactic acid composites is poor, which limits its large-scale promotion and use.
By adjusting the ratio of components such as polylactic acid, talc and polyadipate, the D90 particle size of talc and the melting point of polyadipate, the crystallization speed of polylactic acid composite material is affected, thereby improving its heat resistance.
The heat resistance performance of polylactic acid composite materials has been improved, the thermal deformation temperature is maintained above 85℃, the impact strength reaches above 4.5KJ/m2, and has better heat resistance and toughness.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a polylactic acid composite material and a preparation method thereof. Background Art
[0002] Polylactic acid is a biodegradable polymer prepared by chemical synthesis using renewable plant resources as raw materials. It is a thermoplastic aliphatic polyester with a glass transition temperature of 60°C. It is a hard polymer in a glassy state at room temperature, and its thermal properties are similar to those of polystyrene. Polylactic acid can be processed in various ways like ordinary polymers, such as extrusion, cast film, blown film, injection molding, bottle blowing, fiber molding, etc. Polylactic acid has excellent biocompatibility, antibacterial properties, mechanical properties and processing properties, but it is hard and lacks toughness, poor impact resistance and heat resistance. At this stage, polylactic acid is mainly used as a fast-moving consumable product, which hinders the large-scale promotion and use of polylactic acid materials.
[0003] In the art, aliphatic-aromatic copolyesters such as polybutylene adipate terephthalate are often introduced into polylactic acid composites to improve the toughness of the polylactic acid composites. However, the introduction of aliphatic-aromatic copolyesters does not significantly improve the heat resistance of the polylactic acid composites.
[0004] How to improve the heat resistance of polylactic acid composites while introducing aliphatic-aromatic copolyesters is an important research direction in this field. Summary of the invention
[0005] In order to solve the technical problem of low heat resistance of polylactic acid composite materials in the prior art, the primary purpose of the present invention is to provide a polylactic acid composite material.
[0006] Another object of the present invention is to provide a method for preparing the polylactic acid composite material.
[0007] Another object of the present invention is to provide an application of the polylactic acid composite material.
[0008] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0009] The present invention protects a polylactic acid composite material, comprising the following components in parts by weight:
[0010] 40-95 parts of polylactic acid, 5-40 parts of talc, 1-20 parts of polybutylene adipate terephthalate;
[0011] The particle size D90 of the talc satisfies 10 μm≤D90≤20 μm, and the melting point Z of the polybutylene adipate terephthalate satisfies 110° C.≤Z≤125° C.
[0012] The crystallization speed of the polylactic acid composite material is affected by the formula composition, the particle size of talcum powder, and the melting point of polybutylene adipate terephthalate. Talc powder has the effect of a nucleating agent, and its content and particle size have a greater influence on the crystallization speed of the polylactic acid composite material. Polybutylene adipate terephthalate plays a role of heterogeneous nucleation, which also has a greater influence on the crystallization speed of the polylactic acid composite material. The present invention further affects the speed of the crystallization speed by adjusting the ratio of the three components, the D90 particle size of talcum powder and the melting point of polybutylene adipate terephthalate (PBAT), thereby affecting the heat resistance.
[0013] Preferably, the weight percentage of the polylactic acid in the polylactic acid composite material is not less than 40%.
[0014] Specifically, the particle size D90 of the talc powder may be 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, or 20 μm.
[0015] Preferably, the particle size D90 of the talc powder satisfies 12 μm≤D90≤18 μm, preferably 15 μm.
[0016] In the present invention, the test method for the particle size D90 of talcum powder can be determined by referring to the method of GB / T 19077.1-2008 "Particle size analysis by laser diffraction method".
[0017] Specifically, the melting point Z of the polybutylene adipate terephthalate may be 110°C, 111°C, 112°C, 113°C, 114°C, 115°C, 116°C, 117°C, 118°C, 119°C, 120°C, 121°C, 122°C, 123°C, 124°C, or 125°C.
[0018] In the present invention, the testing method of the melting point Z of polybutylene adipate terephthalate is: DSC test, the sample is first heated from 30°C to 220°C at a heating rate of 10°C / min, and maintained at 220°C for 3 minutes to eliminate the thermal history, then cooled to 30°C at a rate of 10°C / min, and then heated to 220°C at a rate of 10°C / min. The melting point is taken from the second heating curve.
[0019] Preferably, the melting point Z of the polybutylene adipate terephthalate satisfies 112°C≤Z≤122°C, preferably 115°C.
[0020] Specifically, the polybutylene adipate terephthalate of the present invention can be purchased commercially or prepared by oneself. The preparation method can be as follows:
[0021] Esterify excess 1,4-butanediol and terephthalic acid at 240-260°C for 2-5 hours, add adipic acid and carry out esterification reaction at 240-260°C for 2-5 hours, and then carry out polycondensation reaction at 240-260°C for 3-5 hours to obtain the product.
[0022] Specifically, the molar ratio of adipic acid to terephthalic acid is (51-54):(46-49).
[0023] Specifically, the polycondensation reaction is carried out in the presence of a catalyst and a stabilizer.
[0024] More specifically, the catalyst is tetrabutyl titanate, and the stabilizer is phosphorous acid.
[0025] Preferably, the weight average molecular weight N of the polybutylene adipate terephthalate satisfies 80000≤N≤180000 g / mol.
[0026] Specifically, the supercooling degree Y of the polylactic acid composite material satisfies 50° C. ≤ Y ≤ 85° C. In the present invention, the supercooling degree Y is the difference between the melting point Tm (° C.) and the crystallization temperature Tc (° C.) of the polylactic acid composite material.
[0027] In the present invention, the melting point Tm and crystallization temperature Tc of the polylactic acid composite material are tested by DSC test, where the sample is first heated from 30°C to 220°C at a heating rate of 10°C / min, and maintained at 220°C for 3 minutes to eliminate the thermal history, then cooled to 30°C at a rate of 10°C / min, and then heated to 220°C at a rate of 10°C / min. The melting point is taken from the second heating curve, and the crystallization temperature is taken from the cooling curve.
[0028] The present invention further found that by controlling the supercooling degree of the polylactic acid composite material to meet 55°C≤Y≤70°C, the heat deformation temperature of the polylactic acid composite material after post-crystallization treatment is maintained above 85°C and the notched impact strength is maintained at 4.5KJ / m 2 The above has better heat resistance and toughness.
[0029] Preferably, the supercooling degree Y of the polylactic acid composite material is preferably 55°C≤Y≤70°C, specifically 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, preferably 65°C.
[0030] The crystallization speed of polylactic acid is very slow. The present invention performs a post-crystallization treatment on the prepared polylactic acid composite material to accelerate the crystallization speed and improve the heat resistance. Specifically, the post-crystallization treatment includes the following steps: the polylactic acid composite material is made into a strip and baked at 110-130 degrees for 2 minutes to 5 minutes.
[0031] Preferably, the polylactic acid composite material comprises the following components in parts by weight:
[0032] 60-90 parts of polylactic acid, 10-30 parts of talc, and 1-10 parts of polybutylene adipate terephthalate.
[0033] Preferably, the weight average molecular weight M of the polylactic acid satisfies 60000≤M≤250000 g / mol.
[0034] Preferably, the PDLA content of the polylactic acid is ≤2.5%.
[0035] In the present invention, the weight average molecular weight of polybutylene adipate terephthalate and polylactic acid is tested as follows: GPC uses Waters ACQUITY APC TM The equipment was tested at a temperature of 40°C, using XT45, XT200 and XT459 columns, solvent: tetrahydrofuran, mobile phase flow rate: 0.5 mL / min. Polystyrene standards were used as standard samples, and the results were averaged three times.
[0036] Preferably, without affecting the effects of the present invention, the polylactic acid composite material of the present invention may be added with an antioxidant and / or a lubricant according to performance requirements, and the antioxidant and lubricant may be conventional varieties in the art.
[0037] The present invention also protects a method for preparing the above-mentioned polylactic acid composite material, comprising the following steps:
[0038] Polylactic acid, talcum powder and polybutylene adipate terephthalate are uniformly mixed according to a proportion, extruded and granulated to obtain a polylactic acid composite material.
[0039] Preferably, the temperature of the extrusion and granulation is 140-240°C.
[0040] The present invention also protects the use of the polylactic acid composite material in preparing injection molded products.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The polylactic acid composite material provided by the present invention controls the ratio of three components, namely polylactic acid, talcum powder and polybutylene adipate terephthalate, the particle size of talcum powder and the melting point of polybutylene adipate terephthalate, so that the supercooling degree of the polylactic acid composite material is between 50 and 85° C., and a composite material with better heat resistance can be obtained. Under a preferred scheme, the heat deformation temperature of the polylactic acid composite material after post-crystallization treatment is maintained above 80° C. Further controlling the supercooling degree of the polylactic acid composite material between 55 and 70° C. can further increase the heat deformation temperature of the polylactic acid composite material to above 85° C. DETAILED DESCRIPTION
[0043] The present invention is further described below in conjunction with examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually carried out according to conventional conditions in the art or according to the conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets. Any non-substantial changes and substitutions made by those skilled in the art on the basis of the present invention belong to the scope of protection claimed by the present invention.
[0044] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:
[0045] Polylactic acid 1: brand name is PLA 3100D, manufacturer is NATUREWORKS, weight average molecular weight M is around 150000 g / mol;
[0046] Polylactic acid 2: brand PLA 3251D, manufacturer NATUREWORKS, weight average molecular weight M is around 100000 g / mol;
[0047] Polylactic acid 3: brand PLA4032D, manufacturer NATUREWORKS, weight average molecular weight M is around 200000 g / mol;
[0048] Talc was obtained from the following commercial sources, with or without treatment (grinding or sieving):
[0049] Talc 1: Brand TY90-5-A, manufacturer Dongguan Sanzhi, particle size D90 is 15μm;
[0050] Talc 2: Brand TY90-13-A, manufacturer Dongguan Sanzhi, particle size D90 is 10μm;
[0051] Talc 3: Brand TY90-20-A, manufacturer Dongguan Sanzhi, particle size D90 is 20μm;
[0052] Talc 4: Brand SD-9449, manufacturer Liaoning Xinda, particle size D90 is 22μm;
[0053] PBAT 1: Brand name is A400 NC801, manufacturer is Zhuhai Jinfa Biomaterial Co., Ltd., melting point is 118°C, weight average molecular weight is around 100000 g / mol;
[0054] PBAT 2: homemade by Jinfa, melting point 110°C, weight average molecular weight of about 100000 g / mol; preparation method is as follows: 1,4-butanediol (excess) and terephthalic acid are subjected to esterification reaction at 250°C (recorded as temperature T1) for 3.5 hours (recorded as time t1), adipic acid is added to carry out esterification reaction at 250°C (recorded as temperature T2) for 3.5 hours (recorded as time t2), and then catalyst tetrabutyl titanate and stabilizer phosphorous acid are added to carry out condensation reaction at 250°C (recorded as temperature T3) for 3.5 hours (recorded as time t3) to obtain the product, the molar ratio of adipic acid to terephthalic acid is 53.5:46.5.
[0055] PBAT 3: Made by Jinfa, with a melting point of 125°C and a weight-average molecular weight of about 100,000 g / mol. The preparation method is different from that of PBAT2 in that the time t1 is 2 hours, the time t2 is 5 hours, the temperature T3 is 240°C, and the molar ratio of adipic acid to terephthalic acid is 51.5:48.5.
[0056] PBAT 4: Made by Jinfa, melting point 108°C, weight average molecular weight around 100,000 g / mol; the preparation method is different from PBAT2 in that: time t1 is 3 hours, time t3 is 4 hours, temperature T1 is 260°C, and the molar ratio of adipic acid to terephthalic acid is 53.7:46.3.
[0057] PBAT 5: homemade by Jinfa; melting point 126.7°C, weight average molecular weight around 100,000 g / mol; the preparation method is different from PBAT 2 in that: time t2 is 4 hours, temperature T1 is 240°C, temperature T2 is 260°C, and the molar ratio of adipic acid to terephthalic acid is 51.2:48.8.
[0058] PBAT 6: Made by Jinfa, melting point 118°C, weight average molecular weight around 160,000 g / mol; the preparation method is different from PBAT2 in that: time t3 is 5 hours, temperature T2 is 240°C, temperature T3 is 260°C, and the molar ratio of adipic acid to terephthalic acid is 52.4:47.6.
[0059] The polylactic acid composite materials of the embodiments and comparative examples of the present invention are prepared by the following process:
[0060] Polylactic acid, talc and polybutylene adipate terephthalate are uniformly mixed according to a proportion, extruded and granulated at 190° C. in a twin-screw extruder with a length-to-diameter ratio of 40:1 to obtain a polylactic acid composite material.
[0061] The post-crystallization treatment of the polylactic acid composite materials of the embodiments and comparative examples of the present invention before the heat deformation temperature test comprises the following steps:
[0062] The polylactic acid composite material was prepared into a sample bar and baked at 120 degrees for 3 minutes.
[0063] The performance test methods and standards of the polylactic acid composite materials of the embodiments and comparative examples of the present invention are as follows:
[0064] Heat deformation temperature test: refer to the standard "GB / T 1634-2004 Plastic bending load heat deformation temperature test method".
[0065] Toughness test: Reference standard "GB / T 1843-2008 Determination of cantilever beam impact strength of plastics".
[0066] Examples 1 to 15
[0067] This embodiment provides a series of polylactic acid composite materials, and the weight percentage of each component in the formula, the supercooling degree, the heat deformation temperature, etc. of the polylactic acid composite materials are shown in Table 1.
[0068] Table 1 Examples 1 to 15 formulations (parts)
[0069]
[0070] Comparative Examples 1 to 11
[0071] This comparative example provides a series of polylactic acid composite materials, and the weight percentage of each component in the formula, the supercooling degree, the heat deformation temperature, etc. of the polylactic acid composite materials are shown in Table 2.
[0072] Table 2 Formulas of Comparative Examples 1 to 11 (parts)
[0073]
[0074]
[0075] As can be seen from Table 2, the polylactic acid composite materials prepared in Examples 1 to 14 of the present invention all have good heat resistance and toughness, among which Example 1 has the best performance. Comparative Example 1 is modified without adding talcum powder, and its heat deformation temperature and impact strength are greatly reduced; the D90 particle size of talcum powder in Comparative Example 2 is not within the scope of the present invention, and its heat deformation temperature and impact strength are reduced; Comparative Example 3 is modified without adding PBAT, and its heat deformation temperature and impact strength are reduced, and the reduction is relatively large; the melting point of polybutylene adipate terephthalate in Comparative Examples 4-5 is not within the scope of the present invention, and the heat deformation temperature and impact strength are reduced; in other comparative examples, the weight of each component is not within the range set by the present invention, and the heat deformation temperature and impact strength are reduced.
[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polylactic acid composite material, characterized in that: The composition comprises the following components in parts by weight: 40-95 parts of polylactic acid, 5-40 parts of talc, 1-20 parts of polybutylene adipate terephthalate; The particle size D90 of the talc satisfies 10 μm≤D90≤20 μm, and the melting point Z of the polybutylene adipate terephthalate satisfies 110° C.≤Z≤125° C.
2. The polylactic acid composite material according to claim 1, characterized in that: The supercooling degree Y of the polylactic acid composite material satisfies 50°C≤Y≤85°C.
3. The polylactic acid composite material according to claim 2, characterized in that: The supercooling degree Y of the polylactic acid composite material satisfies 55°C≤Y≤70°C.
4. The polylactic acid composite material according to claim 1, characterized in that: The weight average molecular weight M of the polylactic acid satisfies 60000≤M≤250000.
5. The polylactic acid composite material according to claim 1, characterized in that: The weight average molecular weight N of the polybutylene adipate terephthalate satisfies 80000≤N≤180000 g / mol.
6. The polylactic acid composite material according to claim 1, characterized in that: The particle size D90 of the talc powder satisfies 12 μm≤D90≤18 μm.
7. The polylactic acid composite material according to claim 1, characterized in that: The melting point Z of the polybutylene adipate terephthalate satisfies 112°C≤Z≤122°C.
8. The polylactic acid composite material according to claim 1, characterized in that: The polylactic acid composite material comprises the following components in parts by weight: 60-90 parts of polylactic acid, 10-30 parts of talc, and 1-10 parts of polybutylene adipate terephthalate.
9. The method for preparing the polylactic acid composite material according to any one of claims 1 to 8, comprising the following steps: Polylactic acid, talcum powder and polybutylene adipate terephthalate are uniformly mixed according to a proportion, extruded and granulated to obtain a polylactic acid composite material.
10. Use of the polylactic acid composite material according to any one of claims 1 to 8 in injection molded products.